Use of local plants for ecological restoration and slope stability: a possible application in Yan'an, Loess Plateau, China. Issue 1 (1st January 2019) - Xu, Rui; Li, Xunchang; Yang, Wei; Jiang, Chao; Rabiei, Minou
Abstract: This paper aimed to screen the potential species suitable for ecological restoration and slope stability from local natural growing plants in China Loess Plateau under a semiarid climate. As part of the field investigations of local natural growing plants, potential species, which are suitable candidates for ecological restoration and slope stability, were nominated in the hilly-gullied region in the Yan'an area. The results showed that Artemisia spp. is the best candidate to form a stable root-soil composite system to support the loose loess and reinforce the loose soil, particularly suitable as pioneer plant in the initial stage of loess slope ecosystem reconstruction. Field root pull-out test and direct shear test for soil without roots and root-soil composite systems were conducted to analyse the reinforcement effect of Artemisia spp. The results from quantitative analysis of the slope protection effect showed that the slope safety factor could be obviously improved by the growth of Artemisia spp. As the survey, test, stability analysis and case study shown, Artemisia spp. can effectively prevent the occurrence of loess flow slides and shallow landslides, which has extensive application prospect.